Termiticidal Activity of Methanol Extract of Pegagan (Centella asiatica L. Urban) Toward Coptotermes curvignathus Holmgren - Dina Erliana; Charles Banon; Avidlyandi Avidlyandi; Rahmaga Febriansyah; Morina Adfa (Mangifera Edu, 2022)
Termiticide activity of methanol extract of Centella asiatica L. Urban against Coptotermes curvignathus Holmgren was investigated using the no choice test. The chemical components of methanol extract of C. asiatica were identified by GC-MS. The antitermite activity showed that the percentage of termite mortality increased when the concentrations of extract increased. The concentrations of 25% indicated the highest termite mortality which reached 100% on the sixth day. Profiling GC-MS methanol extract of C. asiatica revealed 85 chemical components. Based on MS spectral data, 56 chemical components were identified which were grouped into fatty acids (27.09%), esters (23.73%), hydrocarbons (16.56%), ethers (8.28%), sesquiterpenes (1.61 %), alcohol (1.55 %), aldehydes (3.50%), monoterpenes (1.08%), diterpenes (0.67%), steroids (0.43%), and ketones (0.31 %). Among these, the presence of palmitic acid, patchouli alcohol, and β-caryophyllene may be responsible for its termiticide activity. Other compounds such as triterpenoids, saponins, flavonoids, tannins, steroids, and glycosides that were reported previously not detected by GC-MS in this study, possibly contributing to its activity.